What Do Music Therapists Need to Know Before the Disaster Strikes? - Otera, Masako (Voices: A World Forum for Music Therapy, 2012)
The paper discusses required knowledge in preparation for a disaster relief. The author shares her experience of the Great East Japan Earthquake and reviews how she went through the post-disaster phase as a music therapist. The author has made three suggestions for change in music therapy as a disaster relief. First, specific topics on disaster relief should be included in music therapy educational courses. This should cover general information regarding natural and human-made disasters and disaster relief. Second, making connections with related organizations, both the individual and national level is also suggested. Third, the further accumulation of studies on music therapy as a disaster relief service is needed.